Complementarity between human capital and trade in regional technological progress - Guadalupe Serrano; Enrique Lopez-Bazo; Jose Ramon Garcia-Sanchis (European Regional Science Association (ERSA), 2002)
The effect of openness and trade orientation on economic growth remains a highly contentious issue. Trade facilitates knowledge diffusion and the adoption of more advanced and efficient technologies which faster total factor productivity (TFP) growth and, hence, per capita income. New technologies that diffuse by trade require a sufficiently qualified labour force to adapt them into the domestic productive environment. Thus, openness and human capital accumulation will lead to TFP growth, and the larger the complementarity between both variables the higher TFP growth. The paper discusses the implications of these assumptions and tests their empirical validity using a pool of data for the industrial sector in the Spanish regions in a period in which both the stock of human capital and openness experienced a not able improvement. Key words: trade, human capital, technological progress and regions. JEL category: C23, D24, O33.
Keywords: 330